2019
DOI: 10.3892/ol.2019.11243
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gd2O3‑doped carbon‑11‑choline‑lenvatinib nanoparticles contrast agent PET/CT in the diagnosis of patients with lung cancer

Abstract: Positron emission tomography-computed tomography (PET/CT) is an efficient method for the diagnosis of various types of human cancer. Studies have demonstrated that Gd 2 O 3-doped carbon-11-choline (GdCho) can be used as a contrast nanoparticle for PET/CT in the diagnosis of patients with lung cancer. The aim of the present study was to evaluate the effect of GdCho-lenvatinib nanoparticles contrast-PET/CT (GdCho-Len-PET) in the diagnosis and treatment planning of a cohort of patients suspected of having lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…To overcome the interfere of urinary excretion of FDG, 11 C-choline, 11 C-methionine and 11 C-acetate were studied as alternative tracer for primary BC detection in PET/CT, [ 52 , 53 ]. In addition, a lot of nanoparticles are also constructed as potential radiotracers for PET/CT [ 54 56 ]. Right now, few studies reported the utilization of nanoparticles in BC for PET/CT detection, but we believe they may help overcome the obstacles of current tracers and worth further exploration.…”
Section: Bladder Cancer Diagnosis and Nanotechnologymentioning
confidence: 99%
“…To overcome the interfere of urinary excretion of FDG, 11 C-choline, 11 C-methionine and 11 C-acetate were studied as alternative tracer for primary BC detection in PET/CT, [ 52 , 53 ]. In addition, a lot of nanoparticles are also constructed as potential radiotracers for PET/CT [ 54 56 ]. Right now, few studies reported the utilization of nanoparticles in BC for PET/CT detection, but we believe they may help overcome the obstacles of current tracers and worth further exploration.…”
Section: Bladder Cancer Diagnosis and Nanotechnologymentioning
confidence: 99%